Murine mesothelioma induces locally-proliferating IL-10+TNF-a+CD206-CX3CR1+ M3 macrophages that can be selectively depleted by chemotherapy or immunotherapy - Jackaman, Connie; Yeoh, T.; Acuil, M.; Gardner, Joanne; Nelson, Delia (Landes Bioscience, 2016)
© 2016 Taylor & Francis Group, LLC.We used a murine model to monitor changes to myeloid cell subsets, i.e., myeloid-derived suppressor cells (MDSCs), M1 macrophages that secrete pro-inflammatory cytokines and express CD40 and CD80 and suppressive M2 macrophages that secrete anti-inflammatory cytokines and express CD206 and CX3CR1, during mesothelioma progression and during chemotherapy or immunotherapy-induced tumor regression. In vitro studies showed that mesothelioma-conditioned media generated CD206-CX3CR1+MCP-1+TGF-ß+ macrophages that induced T cell proliferation but prevented T cell IFN? production. In vivo studies showed that co-inoculation of macrophages with mesothelioma cells led to faster tumor growth, and depleting macrophages using anti-F4/80 antibody induced tumor regression. Flow cytometry revealed increasing levels of different suppressive myeloid cells in lymphoid organs: MDSCs dominated bone marrow (BM) and spleens, M2 macrophages dominated tumor-draining lymph nodes (DLN) and a mixed IL-10+TNF-a+CD206-CX3CR1+ M1/M2 (M3) macrophage subset dominated the mesothelioma microenvironment. Ki67 staining and cell cycle analysis showed that tumor-associated M1 and M3, but not M2, macrophages were proliferating in situ, with M1 cells arrested in the G1 phase while M3 cells progressed to mitosis. Immunohistochemistry showed that M1 and M3 cells were co-located supporting the hypothesis that M1 cells transition to M3 cells during proliferation. Gemcitabine reduced tumor-associated M3 and MDSCs, but not M2 macrophages, the latter likely contributing to the tumor outgrowth seen following treatment cessation. In contrast, IL-2/agonist anti-CD40 antibody therapy reduced M3 cells and polarized macrophages into M1 cells coinciding with tumor regression. These data show that myeloid cells, particularly M3 cells, represent a therapeutic target for the generation of antitumor immunity.